The Differential Diagnosis of Hypopigmented Mycosis Fungoides and Vitiligo With Reflectance Confocal Microscopy: A Preliminary Study - Liu, Huaxu; Wang, Leilei; Lin, Yan; Shan, Xiaofeng; Gao, Min (Frontiers in Medicine, 2021)
Objective: To investigate the role of reflectance confocal microscopy(RCM) in the differential diagnosis of Hypo-pigmented mycosis fungoides(HMF) and vitiligo. Methods: Cases with persistent hypo-pigmented patches, suspicious of early stage vitiligo or HMF were imaged with RCM. The melanin contents and inflammatory conditions of the epidermis and superficial dermis of the lesions were compared with the same layers of the adjacent skin, and then, the imaged lesions were biopsied and analyzed by histology. Results: 15 cases were enrolled in this study, and based on the RCM findings, there was just slight or moderate reduction of melanin,but no melanin absence in the basal cell layer of HMF lesions. The finding of monomorphous weakly refractile, oval to round cells on the basis of vesicle-like dark space was clearly elucidated in the epidermis of the lesions by RCM, which indicates the Pautrier's micro-abscesses on histopathology. Among those 15 cases, 13 cases were identified as HMF, and the other 2 cases were vitiligo, based on RCM findings, which were confirmed by histology analysis. Conclusions:The RCM findings correlated well with histology results in the screening of HMF, which indicates the RCM is an important tool in the early detection and differential diagnosis of HMF.